The Effect of Compensation and Job Satisfaction on Employee Motivation at the Office of the KPKNL Bengkulu - Eko Satrea Ade Putra; Karona Cahya Susena; Abdul Rahman (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the effect of compensation and job satisfaction on the work motivation of Bengkulu KPKNL employees. The sample in this study were 33 people at the Bengkulu State Property and Auction Service office. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of multiple linear regression calculations obtained multiple linear regression equation Y = 8,993 + 0,424X1 + 0,381X2 + 6,136(e). The coefficient of determination of the Adjusted R square value is 0.474. This means that X1 (Compensation), and X2 (satisfaction) have an effect on motivation (Y) by 47.4% while the remaining 52.6% is influenced by other variables not examined in this study. The test results for the X1 variable (motivation) show the tcount value is greater than ttable at 2,424 > 1,693 and a significance value of 0.021 < 0.05. Because tcount > ttable and the significance value is less than 0.05, then H0 is rejected and Ha is accepted. This means that X1 (motivation) has a significant influence on work productivity (Y) of employees at PT. Four Lawang Agro Perkasa in Empat Lawang Regency. The test results for the X2 variable (job satisfaction) show the tcount value is greater than ttable at 3.258 > 1.693 and a significance value of 0.003 <0.05. Because tcount > ttable and the significance value is less than 0.05, H0 is rejected and Ha is accepted. This means that X2 (job satisfaction) has a significant effect on work productivity (Y) of employees at PT. Four Lawang Agro Perkasa in Empat Lawang Regency. The value of Fcount > Ftable (22,986 > 3,29) with a significant value of 0.000 < 0.05 indicates that simultaneously X1 (motivation) and X2 (job satisfaction) have a significant effect on work productivity (Y) of employees at PT. Four Lawang Agro Perkasa in Empat Lawang Regency.